A global perspective on inflation and propagation channels - Luca Gattini; Huw Pill; Ludger Schuknecht (Journal of Banking and Financial Economics)
This paper revisits the evidence on monetary policy transmission. It extends the existing literature in three dimensions. First, we attempt to internalise potential international channels of transmission by taking a global perspective. More specifically, we explore global aggregates covering a broader set of countries (ca. 70% per cent of the world economy) and a longer time span (from 1960 to 2013) than previous studies. Second, we broaden the set of transmission channels considered, notably by exploring interactions among monetary variables, inflation and asset prices (including residential property prices). Third, we look at the potential role of public debt in driving price developments, on the grounds underpinned by fiscal theories of the price level. On the basis of a VAR analysis, we find that: (1) global money demand shocks affect global inflation and global commodity prices (which, in turn, impact on inflation); (2) global asset price dynamics respond to financing cost shocks and (very modestly) to shocks to global money demand; and (3) positive house price shocks exert a significant influence on inflation. From a global perspective, the study suggests that an understanding of inflation requires recognition of the externalities that global commodity and asset price developments exert over domestic inflation.